Monophosphoryl lipid A inhibits the cytokine response of endothelial cells challenged with LPS. Issue 6 (August 2015) - Stark, Ryan; Choi, Hyehun; Koch, Stephen; Lamb, Fred; Sherwood, Edward
Monophosphoryl lipid A (MPLA) is a TLR4 agonist that is used as an immunomodulator in human vaccines; additionally, it has been shown to be protective in models of sepsis. As endothelial cells regulate inflammation, we hypothesized that MPLA would decrease activation of human umbilical vein endothelial cells (HUVECs) to LPS. We studied HUVECs challenged with LPS (100 ng/ml), MPLA (0.001–100 µg/ml) or a combination. Secretion of IL-6, RANTES (CCL5) and IP-10 (CXCL10) were assessed by ELISA. Activation of MAPK phosphorylation and cytokine transcription were assessed by Western blot analysis and PCR, respectively. MPLA alone was a weak stimulator of myeloid differentiation primary response protein 88-dependent IL-6 and did not induce TIR-domain-containing adapter-inducing IFN-β (TRIF)-dependent chemokine responses. MPLA significantly reduced LPS-mediated IL-6 production. This inhibitory effect was also conferred for the TRIF-dependent chemokines RANTES and IP-10. Inhibition of LPS-mediated activation by MPLA was associated with reduced p38 phosphorylation and mRNAs encoding inflammatory cytokines. MPLA inhibition of LPS signaling appeared to be at the level of the TLR4 receptor, acting as a receptor antagonist with weak agonistic properties. This study provides evidence of a novel mechanism for the inhibitory effect of MPLA on LPS-induced endothelial activation.